A Primary Hydatid Cyst Infestation as Perianal Abscess: A Case Report - Heshmattolah Soleimani; Mehrdad Seifi; Mehrnoosh Shemshadi (مجله دانشکده پزشکی اصفهان, 2011)
Background: Hydatid cyst is a zoonotic disease caused by infestation of tape worm of the genus echinococcus. The most commonly encountered form of hydatid cyst caused by echinococcus granulosus or dog tapeworm. Liver and lung are usual locations of infestation. Locations other than liver, lung, and spleen are found in 6 percent of patient that most of those are secondary hydatid disease. Primary pelvic occurrence is less than 2 percent. Case Report: we report a rare case of primary hydatid cyst infestation of perianal location in a 56 years old man from a rural area. He presented with an inflammatory mass that seemed to be a perianal abscess. Pathologic report of drained materials confirmed hydatid cyst. Conclusion: It seems to be necessary, especially for physicians working in endemic area such as sheep and cattle-rearing regions, to be more familiar with unusual presentations of hydatid cyst.